MEDIATIZATION OF ISLAMIC DOCTRINE IN A NEW ERA OF DIGITAL INDONESIA: The Case of Ḥadīth on Dajjāl - D. I. Ansusa Putra; Agus Firdaus Chandra (Jurnal Theologia, 2019)
This research is a study of the mediatization of the ḥadīth on Dajjāl (the anti-Christ) in the context of media culture. Mediatization of the ḥadīth through illustrations allows every Muslim to understand the stages and events that will occur at the End of the Time (Ākhir al-Zamān). Such ḥadīth is pre-actual doctrinal texts in Islam. This article uses the theory of mediatization that has a close link with the discipline of media studies and religiosity. We argue that the ḥadīth illustration as an expression of religious beliefs is a continuation of the massive use of technology in understanding religious doctrines. On the other hand, the illustration of the ḥadīth. Ḥadīth on the Dajjāl in digital media has formed a new pattern in the understanding of ḥadīth from abstract-imaginative to concrete-imaginative. The illustration of the Dajjāl has become an indication of the widespread role of the media in the spread of Islamic doctrines, and its changing role from being dominated by the texts to being dominated by the logic of religion. This research uses the theory of mediatization with the approach of media culture. The data is obtained from footage of such ḥadīth documentary airing on YouTube accounts. These shows usually refer to preachers who are concerned with conveying the contents of the ḥadīth.